KOALISI MASYARAKAT SIPIL DALAM ADVOKASI KEBIJAKAN RELOKASI WARGA TAMBAKREJO KOTA SEMARANG - Syofii, Muhammad; Alfirdaus, Laila Kholid (JPP (Jurnal Politik Profetik), 2020)
The development policy of East Flood Canal (BKT)in Semarang City did not work accordingly purposes because it had to deal with settlements along the river banks. In addition, expansion to overcome physical problems, but not focusing enough to the social and economic aspects of society, otherwise emerged new obstacles. These conditions encourage the activism of affected citizens with community of civil society to advocate for policies. This study intended to explain the political advocacy carried out by the civil society coalition in the city of Semarang with the residents of Tambakrejo over the relocation policy. A qualitative method was conducted in this study through interviewing the accompanying actors, documentation and observation. The results of the study showed that coalition advocacy was the key to the presence of various strategies because of the accumulation of resources of each organization that was able to work together rather than compete. In addition, the ability of civil society coalition actors in conducting political relations with policy stakeholders was the key to changing technocratic policies.